UNDERSTANDING LEVEL OF PKK BANJAR PURWA SANTHI BENOA ON MEDICAL MASK WASTE MANAGEMENT AND STRENGTHENING HEALTH PROTOCOLS IN CONTROLLING COVID-19 INFECTION - I Komang Hotra Adiputra; Kadek Diana Harmayani; Ni Made Susilawathi; Cokorda Agung Wahyu Purnamasidhi; Komang Ayu Witarini; I Wayan Arya Biantara; I Dewa Made Sukrama; I Gede Purna Weisnawa; Jerry; Putu Kintan Wulandari; Darren Junior; Dewa Ayu Fony Prema Shanti; I Dewa Ayu Agung Warmadewanthi (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2023)
The increase in mask waste and a lack of understanding about the management of single-use mask waste raises the potential for environmental pollution and COVID-19 transmission. Aim: This study aimed to assess the level of understanding of medical mask waste management and strengthening health protocols in controlling COVID-19 infection in Banjar Purwa Santhi, Benoa, Badung Regency. Methodology and Results: A cross-sectional method and descriptive study design were used with a sample of 100 respondents selected via stratified sampling. The research and service activities at Banjar Purwa Santhi Benoa include public campaign and assessment of the level understanding of medical mask waste management. Based on univariate analysis, 91% of respondents know that mask waste contains hazardous and toxic substances. If mask waste is disposed carelessly, 98% of respondents stated that it can pollute the environment, and 98% of respondents also stated that it has the potential to become a means of transmitting COVID-19. However, 85% of respondents disposed of the masks in the household trash. Conclusion, significance and impact study: Respondents had a good level of knowledge about health protocols and mask waste management but have not separated masks from household waste. By holding the community service activity, it is hoped that changes in community behavior will occur.